The Influence of COVID-19 on Irrational Consumption Behavior in a Chinese Sample: Based on a Serial Mediating Model - Yue-Qian, Hu; Piao, Xie; Ying, Wang; Zhi-Xin, Huang; Yi-Ting, Wu; Hai-Long, Sun (Frontiers in Psychology, 2021)
Based on the scarcity theory, this study focuses on exploring the relationship between the severity of public health emergencies (i.e., COVID-19) and individual irrational consumer behaviors through the serial mediating variables of perceived scarcity and negative mentality. An online questionnaire was used to collect data from participants in China and we obtained 466 effective questionnaires in total. The findings showed that the relationship between each pair of factors – perceived pandemic severity, perceived scarcity, negative mentality and irrational consumption behaviors – was significantly positive. Although the perception of the severity of this public health emergency did not directly predict irrational consumer behavior, the effect was mediated by perceived scarcity and negative mentality independently and serially.These findings reveal that people who strongly perceive scarcity and are prone to negative attitudes are more likely to demonstrate irrational consumer behaviors (such as rushing to buy and hoard living supplies) once the public perceives a public health emergency as severe. This effect occurs because the perceived scarcity that results from the epidemic affects people’s cognition, emotion and behavior.